Depression Degree In Middle Primigravida Who Were Getting Outpatient Treatment In Puri Betik Hati Delivery Hospital In Bandar Lampung - Khairun Nisa; M. Masykur Berawi (Fakultas Kedokteran Universitas Lampung, 2012)
First pregnancy has been considered as a way to dimish a woman's self doubt about her feminity. Changes in their physics, pschycological condition and the experience of pregnancy for the first time in primigravida could give depression. The aim of this research is to know the degree of depression in middle primigravida who were getting outpatient treatment in Puri Betik Hati Delivery Hospital in Bandar Lampung. The benefit of this research to the researcher, the reader and common society is to add insight about depressiom in pregnant women. This research is descriptive research with cross sectional approach. The source of the data used is a primary data of the Beck Depression Inventory (BDI) questionnaire. The result of the research from the 53 respondent is known that there was depression in middle primigravida as many as 18 woman (34%), with mild depression degree as many as 14 women (78%) and middle depression degree as many as 4 women (22%), also known that mild depression mostly happened to the respondent in the first trimester of pregnancy, which was as many as 7 women (39%) and middle degree depression mostly happened in the third trimester of pregnancy, which was as many as 2 women (11%)